Potential savings of potable water due to the use of rainwater in a shopping mall in Recife/PE - Borges, Ana Paula de Lima; Silva, Simone Rosa da; Moura, Micaella Raíssa Falcão de; Vasconcelos, Ricardo Oliveira Bandeira de (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
Water is one of the world's most valuable resources and indispensable for human survival. Given this, climate change and population growth generate an increase in demand for water resources, leading to water scarcity. The use of rainwater is a measure that mitigates environmental impacts, contributes to the retention of rainwater and reduces the demand for drinking water.  Therefore, water scarcity stimulates the development of alternatives for water conservation. The objective of this study is to estimate the potential savings of potable water to be replaced by rainwater for non-potable use in a shopping center building in the Northeast of Brazil. The methodology consisted in simulating the volume of the reservoir for storage of collected rainwater.  A study of the rainfall indexes and their periodicity was carried out, evaluating the months with highest and lowest precipitation. Subsequently, the Neptune computer program was used to determine the volume of the reservoir. To this end, a study was carried out with different catchment areas, in order to define the area that offers the best potential for supplying the water demands. The results indicated that the most suitable reservoir volume is 117 m³, with potential savings of 6.02% for drinking water and a complete and partial supply of 52.56% for rainwater demand. It was concluded that the potential for drinking water savings justifies the implementation of a rainwater harvesting system in a project of this size, proving to be technically feasible.